PERBANDINGAN GAYA KEPEMIMPINAN POLITIK GUBERNUR DKI JAKARTA DALAM PENANGANAN BANJIR DI DKI JAKARTA (Studi Pada Era Joko Widodo, Basuki Tjahaja Purnama Dan Anies Baswedan) - Erika Fajar Novianti (2023)
As a metropolitan city, DKI Jakarta is certain to have various kinds of problems, both disasters and non-disasters. Flooding is one of the problems that until now has not been properly resolved. In fact, this flood disaster is often used as a target for politicization by prospective leaders in DKI Jakarta. Governors as regional heads have their own way of dealing with these problems, such as Joko Widodo (Jokowi), Basuki Tjahaja Purnama (Ahok), and Anies Rasyid Baswedan (Anies). They are big figures who have their own political leadership style in carrying out their roles. This study aims to identify a comparison of the political leadership style of the governor of DKI Jakarta in handling floods in DKI Jakarta by using the theory of leadership concepts and leadership styles according to Ralph White & Ronald Lippit. The method used in this study is descriptive qualitative using primary data sources and secondary data. Data collection techniques were carried out by means of semi-structured in-depth interviews. In this study, the constant comparative method of data analysis was discovered by Glaser & Strauss. The results of this study indicate that there are similarities in the political leadership styles of Joko Widodo and Anies Baswedan which lead to a democratic leadership style while Basuki Tjahaja Purnama leads to an autocratic leadership style. Keywords: Political Leadership Style, Flood Handling, Joko Widodo, Basuki Tjahaja Purnama, Anies Baswedan.